Elevated Plasma von Willebrand Factor Levels Are Associated With Subsequent Ischemic Stroke in Persons With Treated HIV Infection. (21st October 2021) - Graham, Susan M; Nance, Robin M; Chen, Junmei; Le, Jennie; Chung, Dominic W; Wurfel, Mark M; Tirschwell, David L; Zunt, Joseph R; Marra, Christina M; Ho, Emily L; Huffer, Andrew; Chow, Felicia C; et al.
Abstract: Background: We assessed whether key biomarkers of endothelial activation and hemostasis/thrombosis were elevated in individuals receiving effective antiretroviral therapy (ART) in the year before ischemic stroke. Methods: We conducted a case–control study nested in the CFAR Network of Integrated Clinical Systems cohort, comparing 42 adjudicated cases with ischemic stroke with 83 controls matched for ART regimen. Angiopoietin-1, angiopoietin-2, C-reactive protein, interleukin-6, plasminogen activation inhibitor–1, P-selectin, serum amyloid–A, soluble CD14, ICAM-1, VCAM-1, apolipoprotein A1, ADAMTS13, and von Willebrand factor (VWF) were measured in stored plasma collected before the stroke event. We used conditional logistic regression to identify associations with ischemic stroke, with and without adjustment for Atherosclerotic Cardiovascular Disease (ASCVD) and Veterans Aging Cohort Study (VACS) scores. Results: After adjustment for age and sex, higher plasma viral load and higher angiopoeitin-2, soluble CD14, and VWF were associated with increased odds of ischemic stroke; higher nadir CD4 count was associated with decreased odds of ischemic stroke. VWF remained associated with subsequent ischemic stroke after adjustment for ASCVD score (adjusted odds, 1.74; 95% CI, 1.01–2.98 per log2 increment). In a separate model adjusting for VACS score, only VWF (adjusted odds, 1.80; 95% CI, 1.04–3.12 per log2 increment) was associated with subsequent ischemic stroke. In a sensitivity analysis excluding participants with viral load ≥400 copies/mL, associations between VWF and ischemic stroke were attenuated, with risk estimates ranging from 1.59 to 1.64 per log2 increment. Conclusions: Endothelial activation and related release and attachment of VWF may play an important role in ischemic stroke among persons with treated HIV infection.